Two new species of Compositae, Eupatorieae from México - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2013)
Two new Mexican species of Compositae-Eupatorieae are described and illustrated. Brickellia leonis, from Michoacán, belongs to the group formerly recognized as a separate genus Kuhnia, in accordance with its plumose pappus bristles, and seems to be related to B. adenolepis (B. L. Rob.) Shinners. Oxylobus juarezensis, known from a single collection from the Sierra de Juárez of Oaxaca, is more closely related to O. oaxacanus Blake.